Exploratory Research on Good Governance for Vanaprastha Tourism - I Gede Wiwin Suyasa; Sugiarto Sugiarto; Sony Heru Priyatno; Ray Octafian; Tri Suyud (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
Tourism is an open sector, characterized by low barriers to entry and influenced by various political, social, environmental, and technological trends. The concept of governance in the tourism industry has gained significant attention in recent years, as it plays a crucial role in ensuring the sustainable development and competitiveness of tourist destinations. This study presents the findings of an exploratory research study on a good governance model for Vanaprastha Tourism. The research revealed that Vanaprastha Tourism encompasses seven risk factors as a destination concept. These include nature engagement, the experience of silence and contemplation, engagement with traditional practices, a holistic approach to well-being, sustainability and environmental consciousness, cultural immersion and authentic experiences, community empowerment, and socio-economic impact. Assessing the seven factors and overall visitor perception is essential for effective governance in Vanaprastha Tourism. The framework includes eight assessment elements, with 30 indicators and 49 sub-indicators, offering a comprehensive evaluation of various aspects such as environmental sustainability, community engagement, and visitor satisfaction. Vanaprastha Tourism should advocate for responsible tourism practices and foster stakeholder collaboration to address critical challenges. This will allow Vanaprastha Tourism to emerge as a model for sustainable and responsible tourism and safeguard its distinctive cultural and environmental heritage.